Cuidado a pessoa tabagista na pandemia da Covid 19 no município de João Pessoa: análise situacional - Macedo, Kalina Cícera (2022)
Cigarette smoking contributes significantly to several health problems and increases morbidity and mortality of numerous diseases. Although structured smoking cessation programs represent effective strategies to reduce injuries and costs for the health system, moreover, the Brazilian Ministry of Health has implemented the National Plan for Tobacco Control (PNCT), current services have limited scope and have been seriously compromised by the coronavirus disease (COVID-19) pandemic. Objective: To analyse the situation of health services from the smoker care in the city of João Pessoa in the COVID 19 pandemic. Method: A descriptive, qualitative-quantitative study was carried out, consisting of two phases: survey of health indicators, of an exploratory nature, through data from the municipal health secretariat for monitoring the PNCT, and; evaluation of the program from the perspective of health professionals and users. The first phase allowed the situational analysis and consisted of evaluating the numbers of patients seen and the functioning of the services before and during the pandemic. The quantitative data from the second phase were collected from the groups of professionals and users, as well as the qualitative assessment, through a semi-structured questionnaire. Results and discussion: The results pointed to a low coverage of the program in João Pessoa, where about 1% of smokers had access to the program. The study showed a drop in the number of smokers attended in the pandemic. A relatively high effectiveness was observed. In the period evaluated, the program was effective and continuous in only two services of the specialized network, with different professionals involved. The data show a drop-in demand for the program during the pandemic, with only two services performing remote group appointments and meetings. In the qualitative analysis among the negative points after the pandemic, the difficulty of users with remote tools and difficulties with exams and specialized references stands out. Final considerations: The study concludes that the city of João Pessoa has an incipient implementation of the PNCT in PHC. During the COVID 19 pandemic, the number of services offered significantly reduced. Services had reduced demand and actions. More responsibility is needed on the part of health managers, for greater access to the program, especially in PHC.